Quantifying genetic and genotypic gain gaps in Eucalyptus: the hidden cost of ignoring inbreeding and dominance - Araujo, Marcio J.; Bush, David; Tambarussi, Evandro V. [UNESP] (Springer Nature, 2025)
Understanding the mating system of Eucalyptus species is necessary to accurately estimate genetic parameters and improve breeding programs. Eucalyptus species often exhibit mixed mating systems, leading to complex relationships among progenies. Traditional tree breeding programs that assume a half-sibling relationship for open-pollinated (OP) trials may overestimate genetic gains by neglecting the effects of inbreeding and dominance. This study focuses on Eucalyptus pellita, a species with a mixed mating system, to quantify the impact of selfing and dominance on breeding strategies. We simulated OP trial growth data for 100 randomly selected families in a randomized complete block design, using published estimated parameters for diameter at breast height (DBH). Our analysis indicated that marker-based models, particularly those incorporating dominance effects, provide more accurate genetic parameter estimates and larger predicted genetic gains than pedigree-based models. These results reveal pronounced genetic and genotypic gain gaps when traditional models are employed, underscoring the imperative for integrating dominance-informed genomic selection strategies. Thus, our study provides essential guidance for optimizing breeding programs to sustainably enhance productivity and genetic quality in Eucalyptus plantations.